Entrepreneurial intention among university students of a developing economy: the mediating role of access to finance and entrepreneurship program - Mohammad Shibli Shahriar; Md Sharif Hassan; Md Aminul Islam; Farid Ahammad Sobhani; Md Touhidul Islam (Cogent Business & Management, 2024)
This study addresses Bangladesh's unemployment problem and its youth's limited entrepreneurial aspiration focusing on critical factors that influence entrepreneurial intentions among university students in Bangladesh. Recognizing universities' role in fostering entrepreneurship, the study aims to identify these determinants, bridging a gap in literature in the context of Bangladesh. Built upon an extended theory of planned behavior, the study incorporates `access to finance' and `entrepreneurship program' as mediators. This framework examines the relationships of `attitude', `subjective norms', `perceived behavioral control', `entrepreneurship program', `access to finance', and their collective impact on entrepreneurial intentions. Utilizing stratified random sampling, the researchers collected data from 394 students across 23 selected Bangladeshi universities offering entrepreneurship programs encompassing Faculty of Business & Entrepreneurship and Faculty of Science & Engineering. The study employed Structural equation modeling (SEM) for analyzing the data. The findings revealed that there were positive relationships between `entrepreneurial intention' and `attitude', `subjective norms', `perceived behavioral control', `entrepreneurship program', and `access to finance'. The findings have practical implications for Bangladesh's government and educational institutes when it comes to promoting entrepreneurship programs extensively. The empirical results clearly demonstrate that the integration of access to finance and practical entrepreneurship programs significantly boosts the entrepreneurial aspirations of university students, encouraging them to pursue entrepreneurship as a career path. This, in turn, contributes to the advancement of economic sustainability in Bangladesh. These outcomes are consistent with the overarching aims of Sustainable Development Goal 8, which strives to foster continuous economic growth, generate employment prospects, and ensure decent work opportunities, particularly for the youth.
Keywords: 650; Access to finance; entrepreneurship program; attitude; subjective norm; perceived behavioral control; entrepreneurial intention